STRATEGI SANITASI PEMERINTAH KOTA PEKANBARU DI KECAMATAN TAMPAN TAHUN 2015 - Fajar Ramadhani; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Pekanbaru is the capital of Riau province, with an area of approximately 632.26 km2. The total population of approximately 800,000 (2008) rose from 586,000 inhabitants (2000). Population growth rates are an average of 4% per year. Projected population will increase to 1.1 million (2015) and 1.5 million (2026). The highest population density, especially in sub-districts in the city center (Pekanbaru City and Sukajadi), and the tendency of the increasing population in the new residential area (Tampan, Marpoyan Peace, Tenayan Kingdom, etc.).From the research it is known that the environment, culture and social class and group memberships community behavior in District Charming in creating a clean environment in the District Charming is still minimal and lacks experience in keeping the environment clean and still not in accordance with existing rules. Factors affecting Sanitation Strategy Pekanbaru City Government in the District Charming. The attitude of society which holds responsibility for a clean social environment in creating a clean environment and increase public awareness of not littering.Keywords: Strategy, Sanitation, Government of Pekanbaru